Cannabinoid Ester Constituents from High-Potency Cannabis sativa - Ahmed, Safwat A. (J Nat Prod, 2008)
Eleven new cannabinoid esters, together with three known cannabinoid acids and Δ(9)-tetrahydrocannabinol (Δ(9)-THC), were isolated from a high-potency variety of Cannabis sativa. The structures were determined by extensive spectroscopic analyses to be β-fenchyl Δ(9)-tetrahydrocannabinolate (1), epi-bornyl Δ(9)-tetrahydrocannabinolate (2), α-terpenyl Δ(9)-tetrahydrocannabinolate (3), 4-terpenyl Δ(9)-tetrahydrocannabinolate (4), α-cadinyl Δ(9)-tetrahydrocannabinolate (5), γ-eudesmyl Δ(9)-tetrahydrocannabinolate (6), γ-eudesmyl cannabigerolate (7), 4-terpenyl cannabinolate (8), bornyl Δ(9)-tetrahydrocannabinolate (9), α-fenchyl Δ(9)-tetrahydrocannabinolate (10), α-cadinyl cannabigerolate (11), Δ(9)-tetrahydro-cannabinol (Δ(9)-THC), Δ(9)-tetrahydrocannabinolic acid A (Δ(9)-THCA), cannabinolic acid A (CBNA), and cannabigerolic acid (CBGA). Compound 8 showed moderate antimicrobial activity against Candida albicans ATCC 90028 with an IC(50) value of 8.5 μg/mL. CB-1 receptor assay indicated that the esters, as well as the parent acids, are not active.